South American Caenis Stephens (Ephemeroptera, Caenidae), new species and stage descriptions - Molineri, Carlos; Malzacher, Peter (Zootaxa, 2007)
Eight species of Caenis are reported from Argentina, and new records are given for Bolivia, Brazil and Uruguay. The nymphs of five of them are firstly described from reared material: Caenis burmeisteri, C. dominguezi, C. gonseri, C. tenella new combination, and C. ludicra. Female adult stage of all these species (except C. tenella) are also firstly described. The new combination Caenis tenella is proposed, and the name Caenis grimi is here treated as a junior synonym of it. Caenis uruzu new species is described from male imagos and nymphs. New distributional records from Argentina and Uruguay are given. Diagnosis and illustrations to distinguish all the treated species from other Caenis species are proposed. A key to adults and nymphs from Argentinean species of Caenis is provided.